2020
DOI: 10.1073/pnas.2007798117
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin modified Pt(II) metallacycle-based supramolecular hyperbranched polymer assemblies for DOX delivery to liver cancer cells

Abstract: Despite the widespread clinical application of chemotherapeutic anticancer drugs, their adverse side effects and inefficient performances remain ongoing issues. A drug delivery system (DDS) designed for a specific cancer may therefore overcome the drawbacks of single chemotherapeutic drugs and provide precise and synergistical cancer treatment by introducing exclusive stimulus responsiveness and combined chemotherapy properties. Herein, we report the design and synthesis of a supramolecular drug delivery assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…The quantitative results indicated that with the increase of DOX or CPT concentration, the cell viability continued to decrease. In addition, with the addition of CPT, the cell viability of the CPT-DOX group was lower than that of the DOX group and the CPT group under the synergistic action of drugs, which was consistent with related reports [ 38 , 39 ]. The above results proved the effectiveness of the liver cancer-on-a-chip constructed by integrating the hierarchical hydrogel with ordered micro-nano structure and microfluidic chip in drug screening.…”
Section: Resultssupporting
confidence: 92%
“…The quantitative results indicated that with the increase of DOX or CPT concentration, the cell viability continued to decrease. In addition, with the addition of CPT, the cell viability of the CPT-DOX group was lower than that of the DOX group and the CPT group under the synergistic action of drugs, which was consistent with related reports [ 38 , 39 ]. The above results proved the effectiveness of the liver cancer-on-a-chip constructed by integrating the hierarchical hydrogel with ordered micro-nano structure and microfluidic chip in drug screening.…”
Section: Resultssupporting
confidence: 92%
“…Among these, coordination-driven self-assembly (CDSA) provides a powerful strategy for producing metal organic complexes (MOCs) with various sizes, shapes, and metal/ligand stoichiometries (20)(21)(22)(23)(24)(25)(26). To date, diverse MOCs have been developed by coordination between metal ions and organic ligands, and these exhibit superiority over their precursors and can be used in emission units, sensors, and hosts as well as in applications in biomedical diagnosis and catalysis (27)(28)(29)(30)(31)(32)(33)(34). Platinum-based architectures are the most extensively studied of these structures and have undergone the most rapid development, due to their facile synthesis (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…Given the reversible noncovalent bonds embodied in supramolecular polymers, they typically exhibit not only polymer-like properties as bulk materials and in solution, but also dynamic characteristics. These latter attributes often have no parallel in the case of covalent polymers and include inter alia reversible formation, recyclability, and stimulus responsiveness ( 8 26 ), including to anions whose role in the fields of biology, chemistry, energy, and supramolecular chemistry is well appreciated ( 27 42 ). These key features complicate molecular weight determinations, as does the fact that a distribution of molecular weights around an average is generally observed.…”
mentioning
confidence: 99%
“…These key features complicate molecular weight determinations, as does the fact that a distribution of molecular weights around an average is generally observed. Moreover, due to the dynamic nature of noncovalent bonds, the monomers used to create supramolecular polymers can assemble in a variety of aggregation modes ( 7 , 39 ). For instance, when the monomer concentration is low, cyclic species or oligomers are more likely to form.…”
mentioning
confidence: 99%
See 1 more Smart Citation